Jejak Peninggalan dan Narasi Lokal Kerajaan Negeri Padang di Kota Tebing Tinggi: Studi Historis terhadap Warisan Budaya dan Identitas Lokal - Batubara, Maimunah; Achiriah, Achiriah; Harahap, Nursapiah (Medan Resource Center, 2025)
This study explores the historical significance and cultural legacy of the Negeri Padang Kingdom, located in Tebing Tinggi City, Sumatra. The research seeks to answer how the material and immaterial heritage of the kingdom continues to shape the region’s identity. Using a qualitative approach and historical methodology, data were collected through in-depth interviews with local historians and community elders, field observations at heritage sites, and analysis of archival documents. The findings reveal five major historical relics that remain central to the local cultural landscape: the Negeri Padang Royal Palace, Nur Addin Mosque, the Royal Family Cemetery, the Balai Kerapatan (Council Hall), and Padang Stadium. Each site carries deep symbolic and historical meaning, reflecting the kingdom’s social, religious, and political influence in the region. The study underscores the importance of these sites in maintaining cultural continuity and identity among local communities. Furthermore, it contributes to broader scholarly efforts in preserving and documenting regional history and cultural heritage in Eastern Sumatra. The research not only enriches the historiography of local kingdoms in Indonesia but also emphasizes the urgency of safeguarding such legacies amid rapid urban development and modernization.